An update on reverse total shoulder arthroplasty: current indications, new designs, same old problems. Issue 3 (March 2021) - Kozak, Thomas; Bauer, Stefan; Walch, Gilles; Al-karawi, Saad; Blakeney, William
Abstract : Reverse total shoulder arthroplasty (RTSA) was originally developed because of unsatisfactory results with anatomic shoulder arthroplasty options for the majority of degenerative shoulder conditions and fractures. After initial concerns about RTSA longevity, indications were extended to primary osteoarthritis with glenoid deficiency, massive cuff tears in younger patients, fracture, tumour and failed anatomic total shoulder replacement. Traditional RTSA by Grammont has undergone a number of iterations such as glenoid lateralization, reduced neck-shaft angle, modular, stemless components and onlay systems. The incidence of complications such as dislocation, notching and acromial fractures has also evolved. Computer navigation, 3D planning and patient-specific implantation have been in use for several years and mixed-reality guided implantation is currently being trialled. Controversies in RTSA include lateralization, stemless humeral components, subscapularis repair and treatment of acromial fractures. Cite this article: EFORT Open Rev 2021;6:189-201. DOI: 10.1302/2058-5241.6.200085